1999
DOI: 10.1007/s001980050144
|View full text |Cite
|
Sign up to set email alerts
|

International Variation in the Incidence of Hip Fractures: Cross-National Project on Osteoporosis for the World Health Organization Program for Research on Aging

Abstract: A cross-national study of hip fracture incidence was carried out in five geographic areas--Beijing, China; Budapest, Hungary; Hong Kong; Porto Alegre, Brazil; and Reykjavik, Iceland--during the years 1990-1992. Cases of hip fracture among women and men of age 20 years and older were identified using hospital discharge data in conjunction with medical records, operating room logs, and radiology logs. Estimated incidence rates varied widely, with Beijing reporting the lowest rates (age-adjusted rate per 100,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(106 citation statements)
references
References 20 publications
6
92
0
8
Order By: Relevance
“…The incidence rates in this study are similar to previously reported European incidence rates [22], although slightly lower than the Scandinavian values [17,18] and the rates from the United States of America [21]. However, the values are greater than those reported in the multinational study by Schwartz et al [22] and to those from other parts of the world, such as the Mediterranean countries [1] or the African countries [25].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The incidence rates in this study are similar to previously reported European incidence rates [22], although slightly lower than the Scandinavian values [17,18] and the rates from the United States of America [21]. However, the values are greater than those reported in the multinational study by Schwartz et al [22] and to those from other parts of the world, such as the Mediterranean countries [1] or the African countries [25].…”
Section: Discussionsupporting
confidence: 85%
“…This higher proportion of women has been explained by the higher incidence of osteoporosis among women and by aging. The incidence rates of hip fractures increase exponentially with age [1,4,18,19,22,25]. In our study, almost 50% of hip fractures appeared in people aged 80-90 years.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Epidemiological studies suggest that populations with high soy intake (such as Asian populations) have a lower incidence of osteoporotic fractures (Adlercreutz & Mazur, 1997;Schwartz et al, 1999). Asian women typically consume about 20g of soy daily which provides 40 mg of isoflavones (Chen et al, 1999;Ho et al, 2003).…”
Section: Isoflavone-containing Soy Proteinmentioning
confidence: 99%
“…1,2 These occur with higher frequency in places where there is a greater proportion of trabecular bone, since this type of bone has a higher rate of remodeling than shown by cortical bone, and it is more susceptible to estrogen deficiency. 2,3 Increasing prevalence of osteoporosis is projected around the world as a result of growing life expectancy and the consequent increase in the elderly population. It is the most common metabolic disease and the main cause of fractures due to skeletal fragility, and is considered to be one of the main public health problems because of the individual and social repercussions.…”
Section: Introductionmentioning
confidence: 99%